족저 내측부의 동정맥 기형: 증례 보고 - 하대호; 권정남; 김유미; 이준형; Ha, Dae-Ho; Kwon, Jung-Nam; Kim, Yu-Mi; Lee, Jun-Hyung (대한족부족관절학회지, 2016)
Arteriovenous malformation (A-V malformation) is defined as an abnormal connection between arteries and veins that lead to A-V shunting with an intervening network of vessels. A-V malformation is a rare condition, and spontaneous regression is also rare. A-V malformation becomes symptomatic when the surrounding tissue and osseous structures are negatively affected. A-V malformation has a high recurrence rate and is relatively hard to treat. In this case, a huge mass with pulsatile and bruit on the medial plantar area were observed. With the diagnosis of A-V malformation in accordance with the results from ultrasonography, magnetic resonance imaging and computed tomography angiography, and mass excision with feeding vessel ligation through plantar midfoot approach was completed successfully.